2011
DOI: 10.1136/ard.2010.145946
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of active ankylosing spondylitis with abatacept: an open-label, 24-week pilot study

Abstract: In this pilot open-label AS study a major response was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 18 publications
2
81
0
6
Order By: Relevance
“…Recently, Song and colleagues studied the efficacy of ABA in 30 patients with AS (15 TNF-α-inhibitor-naive patients and 15 nonresponders to TNF-α inhibitors) and demonstrated that ASAS-40 was reached by 13% of the TNF-α-inhibitor-naive patients and by none of the nonresponders to TNF-α inhibitors [Song et al 2011]. More recently, Lekpa and colleagues showed the lack of efficacy of ABA in axial SpA [Lekpa et al 2012a].…”
Section: Biological Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Song and colleagues studied the efficacy of ABA in 30 patients with AS (15 TNF-α-inhibitor-naive patients and 15 nonresponders to TNF-α inhibitors) and demonstrated that ASAS-40 was reached by 13% of the TNF-α-inhibitor-naive patients and by none of the nonresponders to TNF-α inhibitors [Song et al 2011]. More recently, Lekpa and colleagues showed the lack of efficacy of ABA in axial SpA [Lekpa et al 2012a].…”
Section: Biological Therapiesmentioning
confidence: 99%
“…According to the recommendations of the Assessment of Spondyloarthritis International Society (ASAS) and the European League Against Rheumatism (EULAR), the first-line therapy of SpA is represented by nonsteroidal anti-inflammatory drugs (NSAIDs) and nonpharmacological treatment [Wendling et al 2014;Braun et al 2011]. NSAID therapy effectively controls joint symptoms and signs of axial involvement [Escalas et al 2010;Benhamou et al 2010], giving no significant effects on laboratory markers of inflammation [Escalas et al 2010]; moreover, some studies suggest NSAIDs have beneficial effect on axial structural damage [Wendling, 2013].…”
Section: From Nonsteroidal Anti-inflammatory Drugs To Traditional Dismentioning
confidence: 99%
“…45 No evidence currently supports efficacy of other biologics in AS. An open-label study of abatacept did not show evidence of major response, 46 and rituximab was ineffective in patients who had failed to respond to TNF inhibitors, but clinically significant responses were seen in TNF inhibitor-naïve patients. 47 DMARDs and NSAIDs have been implicated in liver damage.…”
Section: New Biologicsmentioning
confidence: 99%
“…One of the newer TNF-blocking agents, certolizumab pegol, has not been studied in patients with SpA. Other biological agents, such as interleukin-1 receptor antagonist (anakinra), rituximab, tocilizumab and abatacept, have only been studied in small groups of patients with SpA and did not show much efficacy [Tan et al 2004;Haibel et al 2005;Song et al 2010Song et al , 2011aLekpa et al 2012].…”
Section: General Treatment Of Spondyloarthritismentioning
confidence: 99%